Characterization of antibacterial compounds from ganoderma boninense - Syahriel Abdullah (2018)
The organic semiconductors potentially offer attractive characteristics, such as low-temperature fabrication, flexibility deposition technique, low-cost processing, and light-weight, which can be used as an active component in a wide range of electronic applications. Recently, organic semiconductors have gained the attention to facilitate formation of thin film by using solution-processed deposition techniques. The solution-processable organic material such as poly(triarylamine) (PTAA) and 6,13-bis(triisopropylsilylethynyl)-pentacene (TIPS-pentacene) have been reported to exhibit low mobilities, which far comparable to that of vacuum-deposited organic semiconductors mainly due to the morphology of thin films. To achieve device performance to a higher level, morphology design and control by varying spin-coating condition such as spin speed is crucial. The MOM diode was designed by forming a PTAA-TIPS-pentacene layer based on the concentration of TIPS-pentacene, i.e. 0 %, 5 %, 10 %, 15 %, and 20 % in PTAA, between the indium tin oxide (ITO) electrode layer and the counter aluminium (Al) metal layer. X-ray diffraction (XRD) patterns revealed that with the intensity of diffraction peak for PTAA was increased by increasing the pentacene molecules in PTAA. This indicated that there is a binder effect between PTAA and TIPS-pentacene enhance the molecule ordering. Furthermore, the current-voltage (I-V) characteristics were measured using Keithley 2400 source meter unit from -10 to +10 V. Meanwhile, the frequency dependent electrical characteristics were measured using a precision LCR meter in the frequency up to 100 kHz. The turn-on voltage varies from 2.16 to 2.48 V depending on the concentration of TIPS-pentacene in PTAA semiconductors, respectively. The frequency dependence of the electrical responses is attributed to the distribution density of interface states that could follow the alternating current (AC) signal. Investigation exposed that conductance was strongly dependent on the frequency and bias voltage. The capacitance and series resistance were dependent up to constant value at the low frequency region (< 1 kHz), but the capacitance and series resistance were independent at high frequencies (< 100 kHz). The MOM diode showed the positive clamping circuit, where the diode discharges when input voltage in the negative side and charging when input voltage is positive side. In conclusion, blending small molecule organic semiconductors into semiconducting polymer have shown the improvement in electrical properties due to the influence of polymer binding on thin film uniformity and operational stability.